Developing and sustaining adult learners - Boden, Carrie J.; King, Kathleen P., 1958-; Russ, Lauren; Cavazos, Nora (Adult education special topics., 2014)
Developing and Sustaining Adult Learners is the second volume in a series of scholarly publications associated with the annual Adult Higher Education Alliance (AHEA, The Alliance) conference. The title of this volume, derived from the theme of the 2012 conference co-sponsored by American Association of Adult and Continuing Education (AAACE) in Las Vegas, NV, encompasses significant issues and questions at the forefront of the field of adult education. At the conference, scholars, practitioners, and adult educators gave presentations and received feedback on some of the most significant and timely issues in their praxis. The Alliance, which values collaboration, transformative dialogue, and collegiality among professionals, considers this volume a continuation of those conversations as the presentations were expanded into chapters. We are glad that you are joining the conversation.This volume confirms not only that adult learning, higher education, and both fields of research have many contexts, but also that there is so much more to learn about different perspectives and opportunities for research and practice. Opportunities for symbiotic relationship abound. We hope that Developing and Sustaining Adult Learners will be a book that you pull off your bookshelf, or open in your e-reader, often. We know that as we engage in program and course planning, design and teaching, this book will provide needed refreshment and new vision. When research ideas seem too similar, this volume will also provide many seeds for new opportunities.